Revisiting the Universality of Multiple Intelligences Theory in English Writing Classroom: Putting Theory Into Practice - Rukmana Fachrul Islam (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
The present study was undertaken based on an assumption that there is no full guarantee that the university-level students from English department could be easily successful in writing activities. This might be as a result of differences in individuals’ characteristics contributing to language learning process, and even better it has something to do with the so-called “Intelligence”. While some relevant studies concerned about the relationship between the students’ Multiple Intelligence profile and their ability in language learning, the current findings contradicted the findings that of researches. In relation with writing skill, some show a significant correlation, some found only partial correlation, and some illustrated insignificant correlation between the observed variables. To have a clearer picture as to this arguable issue, the present study’s aim was about to look into the relationship between multiple intelligences as a whole part and linguistic intelligence as a part of multiple intelligences, and writing performance of English department students in a state university. This study employed mix method and the instruments applied were MI Inventory, a writing scale adopted from IELTS writing task 2, and interview. A small number of students, 27 students, actively participated in this study, and the findings indicated that insignificant correlation existed between students’ writing performance and their MI profile as a whole part or as independent intelligence, namely linguistic intelligence.